Transfer provisions in islamic jurisprudence and iraqi law: A comparative study - Faris Ali Mustafa (QALAAI ZANIST SCIENTIFIC JOURNAL, 2020)
This study seeks to explain the ruling (contemporary humiliations of Provisions, status in Islamic jurisprudence) and Islamic Sharia has been adhering to the conditions of the creditor and the debtor because the Islamic Shari”a rules its rulings on the basis of the kindness of people contrare to the positive laws The research deals with the definition of hawala language and terminologe In Islamic law and to highlight types of hawala and knowledge 0f contemporare hawala and the researcher approach in his study descriptive approach in monitoring the relevant information descriptive method and accurate description expressed then analyzed accuratyle according to the information contained in banks and found that the right to Islamic law based on the full compatibility of all human rights related to the creditore and the debtor and also found that the Lslamic Sharia preceded other laws and statutes to approver the right of transfer between neighborhoods.